Interrogating masculinity, gender performance, and power dynamics in Indonesian society through Taylor Swift’s ‘The Man’ - Kiram, Muhammad Zawil (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This article examines masculinity, gender roles, and power relations in Indonesian society through Taylor Swift’s song “The Man”. The lyrics and music video, which criticise the demands and double standards that society places on women in comparison to males, provide a framework for analysing related problems in Indonesia, a country where traditional gender roles are ingrained in the fabric of culture. The qualitative content analysis was employed to systematically evaluate the content of “The Man” within various forms of communication, such as texts, images, and videos. The analysis sheds light on the social forces that influence gender performance and the maintenance of male dominance, highlighting how Swift’s critique of gendered power inequalities may be utilised to comprehend the intricacies of masculinity and femininity in Indonesia. The article also highlights the idea of gender performance, taking into account how people in Indonesia either comply with or defy these social norms. Swift’s depiction of a society in which people would view her activities differently if she were a man is reminiscent of the experiences of numerous Indonesian women in both public and private settings. The article then concludes how these gendered expectations reinforce power relations and maintain disparities that most likely benefit men.